Distribution, Growth and Yield of Santalum album L. in Karnataka, India - Divakara, B. N.; Tewari, V. P. (Indian Forester, 2021)
Santalum album L. is distributed from Indonesia in the West to Juan Fernandez Islands in the East and from Hawaiian Archipelago in the North to New Zealand in the South. Sandalwood is one of the most important economic tree species harvested mainly for its heartwood and oil and is used in India from the earliest historic times. The sandalwood stands are under immense pressure and their management is becoming increasingly complex. Unfortunately, efforts aimed at conserving the genetic resources of sandalwood suffer from want of precise information on the area coverage, present status, growth characteristics and diameter size class distribution. In Karnataka, S. album is mainly found in Shimoga, Chickamagalur, Coorg, Hassan, Mysore, Dharwad, Bangalore, Kolar, Belguam, Uttar Kannada, Dakshin Kannada, Bellary and Tumkur districts. Keeping this in view, 41 sample plots were layed-out in sandal wood estates under Karnataka Forest Department. Out of 41 plots, 19 plots were laid out in sandalwood plantations (plantation plots), 4 plots were laid in regeneration plot and 18 plots are natural plots. The younger age plantations (3 - 6 years) are seen in Kadur, Bidar, Bangarpete, Srinivaspur, Malur, Mysore, Dharwad, Yelawala, and Kaggalipura ranges. Older plantation (15 - 20 years) are seen in Ambligola, Shkaripura, Shiralkoppa, Bangalore, Dundsi, Dharwad and JB kaval range. Significant variation in height and diameter growth was observed in all the sampled plots. Growth in Bangalore forest range was superior with 10.39 m of height and 11.52 cm of dbh compared to other ranges having natural distribution. Among the older trees grown under natural conditions, trees in Kadur range showed better height of 7.8 m and diameter of 8.31 cm.